The History Of Physical Training Reforms In Uzbekistan (1991-2019) (Zien Journal of Social Sciences and Humanities, 2025)
In the article analyzes the history of reforms in physical culture in Uzbekistan in 1991-2019 and its main aspects using data from the scientific literature. At the same time, the achievements of athletes in the country and in the international arena are described in detail in the work